Farm visit U Germany (Karakul Circulations: Colonial Economies and the Un_Making of Disciplinary Knowledges in Germany and Namibia, 2020)
169 JPEG files of a visit to a Karakul farm in Germany
Keywords: Karakul sheep; Sheep; Postcolonialism; South Africa; Agriculture; Colonisation; East Germany; Namibia; Swakara; Karakul Circulations; Colonial Economies; Karakul Farming; Germany; Colonial South-West Africa; German Colonialism; Karakul Sheep Industry